EFEKTIVITAS PELAYANAN PADA KANTOR PELAYANAN PERIZINAN TERPADU DAN PENANAMAN MODAL ( KP2TPM ) KOTA PARIAMAN - Yunita Asria; Zaili Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Effectiveness of services is the ability to perform the duties and functionsof the public service of an organization that there is no pressure or tensionbetween implementation. All the people who get the service would want a servicethat is effective especially in the service of the Office of Integrated LicensingServices and Investment ( KP2TPM ) Pariaman City .The research aimed to determine the effectiveness of services in theOffice of Integrated Licensing Services and Investment ( KP2TPM ) PariamanCity . According to Duncan , there are three criteria for measuring theeffectiveness of the Achievement of Objectives , Integration and Adaptation .While the factors that influence the effectiveness of services ie Leadership ,Resources Apparatus , Awareness and Infrastructures . This study uses descriptivequalitative research method that analysis seeks to provide a detailed descriptionis based on the fact that ditemkan in the field , then the presentation of data candescribe the results of interviews and observations will then be deduced.The results of this study indicate that the Office of Integrated LicensingServices and Investment ( KP2TPM ) have been effective in providing services tothe public although there are still limitations such as the lack of the number ofemployees who work in KP2TPM . Nevertheless , KP2TPM continue to provideservices to the community ang maximum so that people get satisfaction in theservice.Keywords : Effectiveness , Services , Organizations